Dr. Sagid Kimpaev — Deep Plane Facelift — Moscow - Kimpaev, Sagid (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Sagid Kimpaev, practicing in Moscow, Russia. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003087; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; russia; moscow